Methods for diagnosing the effectiveness of the enterprise’s financial strategy in the strategy controlling system - Reta, M. V.; Druhova, Elena; Lisnichuk, Oksana (Baltija Publishing, Latvia, 2018)
The purpose of the article is to describe how the controlling system is implemented and controlling tools are applied at enterprises in Ukraine. The article contains selected results of the survey research conducted by the authors at logistics enterprises in Ukraine. The obtained data were used to verify the hypotheses and to evaluate the controlling system implementation at the pharmaceutical companies in Ukraine. Methodology. To substantiate the essence of management accounting tools, the authors used the method of grouping of management accounting tools, affecting the achievement of its goals. The results of the empirical study show that almost half of the surveyed logistics companies use controlling systems in business practice. These are primarily large and medium logistics enterprises regarding employment scope and annual sales revenue. The companies applying the controlling system, as well as the business entities without it actually use operational (traditional) controlling tools, e.g. traditional cost accounting systems complemented by the selected strategic method of controlling. Conclusion. The proposed classification of management accounting tools permits to organize the terminological apparatus of the management accounting system in general and at enterprises in particular.
Keywords: strategic controlling; strategic management; controlling tools; solutions in controlling; strategic method of controlling; controlling system; strategic scorecard; unclear plurals; level; system of indexes; finance